Pathology Consultation on HbA1c Methods and Interferences. Issue 1 (1st January 2014) - Rhea, Jeanne M.; Molinaro, Ross
Abstract: Objectives: To review the various hemoglobin (Hb) A1c methods, with a focus on interferences resulting from Hb variants. Methods: HbA1c is a marker used for the diagnosis and management of diabetes. Each available HbA1c method has advantages and challenges, such as its susceptibility to interferences. Results: The presence of Hb variants and/or abnormalities in RBC turnover cannot only interfere analytically with HbA1c measurements but also may affect the clinical interpretation of HbA1c values. Conclusions: Familiarity with the advantages and challenges of the various methods used for HbA1c testing is essential when establishing therapeutic management and goals based on HbA1c results, especially in populations with a high prevalence of Hb variants.